Analisis Kesalahan Sintaksis Pada Teks Dalam Buku Paket Bahasa Indonesia Kelas X Sma Kurikulum 2013 - Setiyaningsih, Nike Ari; , Prof. Dr. Abdul Ngalim, M.Hum (2016)
This study aimed to describe the forms of syntax errors in textbooks Indonesia class X High School Curriculum 2013 and its improvement. The method used this research is descriptive qualitative method. The data in this study is the text of the report on the observation, text procedures, text exposition, text anecdotes, and the text negotiating. Sources of data in this research the textbook Indonesia class X high school curriculum 2013. The data collection technique used is the classification of the data, then the data is analyzed by composing of sentences into sentences raw. Based on the results of data analysis can be seen that the error analysis in the field of pharases found in the text in textbooks Indonesia class X High School Curriculum 2013 a number of 23 data, which in terms of the use of the element of excessive (wasteful) there are 7 data, in terms of the use of the superlative form which there are 10 data redundant, and in terms of the double penjamakan there are 6 data. Meanwhile, analysis of errors in the field of sentences in the text in textbooks Indonesian tenth grade high school curriculum in 2013 a number of 48 data, which in terms of the sentence not be subject there are 6 of data, in terms of a sentence is not predicated there are 2 data, in terms of the sentence not be subject and predicate (sentence stump) there are 4 records, in terms of a sentence that is not logical there are 4 records, in terms of sentence ambiguity there are 2 data, in terms of the removal of conjunctions are 4 records, in terms of the use of conjunctions excessive are 9 data, in terms of the use of foreign terms there are 6 data, and in terms of the removal of punctuation there are 11 data. Keywords: syntax, phrase, sentence